Outcomes of patients diagnosed with acute myeloid leukemia after solid organ transplantation. Issue 9 (9th August 2017) - Lontos, Konstantinos; Agha, Mounzer; Raptis, Anastasios; Hou, Jing‐Zhou; Farah, Rafic; Redner, Robert L.; Im, Annie; Dorritie, Kathleen A.; Sehgal, Alison; Rossetti, James; Saul, Melissa; Gooding, William E.; et al.
Abstract: Organ transplant recipients are at an increased risk for subsequent cancer including acute myeloid leukemia (AML). Treatment of AML following solid transplantation represents a clinical challenge as most patients have significant comorbidities at the time of AML diagnosis. In this study, we evaluated the treatment and outcomes of patients who developed AML following solid organ transplantation at our institution and reviewed the literature on outcomes for these patients. The study cohort consisted of 14 patients (median age 66 years, range 52‐77 years) with newly diagnosed AML following solid organ transplantation. The median interval time between solid organ transplantation and AML diagnosis was 72 months (range 15‐368 months). Seven patients received standard induction chemotherapy, four patients received intermediate type therapy, and the remaining three patients were deemed not fit for therapy and received palliative and supportive care. Six of the 11 treated patients (55%) achieved complete remission (CR). The median overall survival (OS) for all patients was 6 months. The median OS for the patients who achieved complete remission after therapy was 17 months and 2 months for the remaining patients. Despite initial CR, relapse rates are still high, suggesting that alternative strategies for post‐remission therapies are warranted.